2016
DOI: 10.1093/ijnp/pyw064
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Susceptible Loci and Enriched Pathways for Bipolar II Disorder Using Genome-Wide Association Studies

Abstract: Background:This study aimed to identify susceptible loci and enriched pathways for bipolar disorder subtype II.Methods:We conducted a genome-wide association scan in discovery samples with 189 bipolar disorder subtype II patients and 1773 controls, and replication samples with 283 bipolar disorder subtype II patients and 500 controls in a Taiwanese Han population using Affymetrix Axiom Genome-Wide CHB1 Array. We performed single-marker and gene-based association analyses, as well as calculated polygeneic risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 70 publications
0
15
1
Order By: Relevance
“…The pathway associated with substance dependence (morphine addiction signalling) has never been related to BD; however, because BD is a common comorbid condition with substance use disorder, common genetic underpinnings may be present. Our findings did not replicate the signalling pathways for BD-II identified by Kao et al 46 , probably because of the different approaches implemented. We used candidate miRNAs, whereas Kao et al used single nucleotide polymorphisms identified from genome-wide association scans.…”
Section: Discussioncontrasting
confidence: 99%
“…The pathway associated with substance dependence (morphine addiction signalling) has never been related to BD; however, because BD is a common comorbid condition with substance use disorder, common genetic underpinnings may be present. Our findings did not replicate the signalling pathways for BD-II identified by Kao et al 46 , probably because of the different approaches implemented. We used candidate miRNAs, whereas Kao et al used single nucleotide polymorphisms identified from genome-wide association scans.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to CACNA1C and CACNAB2 , EFHD1 functions as a novel mitochondrial Ca2+ sensor underlying Ca2+-dependent activation of mitoflashes, and was identified as associated with risk to SCZ in a family-based GWAS strategy in an enlarged, ethnically homogeneous, Arab-Israeli family sample (Alkelai et al, 2011; Hou et al, 2016). The ETF1 gene, located in the 5q31, plays important roles in regulating the activity in the translational termination process and transcriptional regulation, and has been reported as a novel susceptible gene for pure BP-II in the latest research literature (Kao et al, 2016; Larkin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“… 41 PKP4 is involved in the regulation of cell adhesion and cytoskeletal organization. 42 In pathway analyses of PGC GWAS data, cell adhesion was associated with BIP, 43 and SCZ, 44 whereas cell junction was implicated in MDD, as well as in an integrative pathway analysis of all three disorders. 45 …”
Section: Discussionmentioning
confidence: 99%